Effects of MFG-E8 expression on the biological characteristics of ovarian cancer cells via the AKT/mTOR/S6K signalling pathway - Na Li; Yazhuo Wang; Lin Liu; Pei Wang; Xiaohua Wu (Taylor & Francis Group, 2023)
In this study, we assessed the effects of MFG-E8 on the biological characteristics of ovarian cancer cells and explored the underlying mechanisms. Human ovarian cancer SKOV3 cells were transfected with MFG-E8 siRNA or NC siRNA. CCK-8, cell adhesion, scratch-wound, and Transwell assays were used to detect changes in cell metastatic processes. Effects of MFG-E8 silencing on the proteins involved in AKT/mTOR/S6K signalling pathway were assessed using qRT-PCR and Western blotting. Transient silencing of MFG-E8 in SKOV3 cells decreased cell proliferation and downregulated the expression of CDK4, cyclin D1, and caspase-3 proteins. Cell adhesion, migration, and invasion were also suppressed. p-AKT, p-mTORC1, and p-p70S6K levels decreased following MFG-E8 knockdown. Hence, MFG-E8 enhances carcinogenesis and affects the AKT/mTOR/S6K signalling pathway in ovarian cancer cells. In conclusion, our results suggested that MFG-E8 could promote ovarian cancer via AKT/mTOR/S6K signalling pathway which improved our understanding of the molecular mechanisms involved in ovarian cancer.IMPACT STATEMENT What is already known on this subject? Milk fat globule-epidermal growth factor 8 (MFG-E8) is expressed in several types of cancers such as oesophageal, breast, and liver. However, the mechanism of MFG-E8 involving in EOC remains unknown. We previously found that MFG-E8 expression was related to pathological staging, tissue differentiation, platinum sensitivity, ascites state, and other clinicopathological characteristics. What the results of this study add? Due to a series of in vitro studies, we confirmed that MFG-E8 is involved in the process of proliferation, invasion and metastasis. Our results show that silencing MFG-E8 can significantly inhibit the expression of cyclin D1 and CDK4 in EOC SKOV3 cells. MFG-E8 enhances carcinogenesis and affects the AKT/mTOR/S6K signaling pathway in ovarian cancer. What the implications are of these findings for clinical practice and/or further research? Taken together, our findings suggest that MFG-E8 may be an oncogene in EOC and provide new insights into the mechanism of MFG-E8 in the progression of EOC.